State-level disparities in burden of ischemic heart diseases mortality attributable to ambient fine particulate matter in the United States, 1990–2019: Observational analysis for the Global Burden of Disease (2019) study. (January 2023) - Yan, Mengmeng
Abstract: Background: ambient fine particulate air pollution (PM2.5) is an important yet often overlooked risk factor for cardiovascular disease in the United States. However, epidemiologic evidence suggests that current knowledge does not comprehensively capture state-level disparities in mortality for ambient PM2.5-related ischemic heart diseases. Methods: I performed serial cross sectional analysis with ambient PM2.5-attributable ischemic heart diseases decedents between 1990 and 2019. I used the Global Health Data Exchange to extract age adjusted mortality rates in each state, and used Joinpoint software to calculate average annual percentage change. Results: the average age adjusted mortality rates (AAMR) for ischemic heart diseases attributable to ambient PM2.5 for both sex ranged from 1.5 (1.3–1.8) per 100, 000 in Hawaii to 1.1 (0.9–1.3) per 100, 000 in Mississippi, respectively. The rate of change in AAMR varied widely across states. Compared with the national level, the number of states with smaller decline has increased from 3 before 2002 to 10 after 2011. Oregon, Idaho, and Montana showed an upward trend in AAMR, which was independent of sex after 2011. Between 1990 and 2019, average AAMR for ischemic heart diseases attributable to ambient PM2.5 was higher for male than female in all states. But the number of states with sex disparities in the rate of change has decreased, from 13 in 1990–2002 to 5 after 2011. Conclusions: wide state-level disparities exist in burden of ischemic heart diseases attributable to ambient PM2.5. After 2011, the association between rate of AAMR decline and sex weakened across states. State-level policies and programs are needed to address the avoidable burden of ischemic heart diseases deaths attributable to ambient particulate pollution, with priority for states with a higher burden. Graphical abstract: Image 1 Highlights: Oregon, Idaho, and Montana saw an upward trend in age adjusted mortality rates. Female in the District of Columbia, Kansas, and Texas saw greater declines than male after 2011. The rate of decline in age adjusted mortality rates in three states was below the national level.